Penajaman Kontras Citra Fotografi Dengan Menggunakan Metode Gram-Schmidt - Mhd Chairul (Resolusi : Rekayasa Teknik Informatika dan Informasi, 2020)
Camera or photo equipment is used by every user both individuals and agencies to get the information needed in a way that is easier and faster to meet all needs and assist activities in solving problems related to requiring computer assistance. Photographic imagery is a two-dimensional image that is produced from a continuous two-dimensional analog image into a discrete image through a sampling process. Analog images are divided into N rows and M columns so that they become discrete images. Crosses between certain rows and columns are called pixels. An example is the image / discrete point on row n and column m is called pixel. By increasing the contrast of the image in a photographic image can make the quality of the image contrast even better with the gram-schmidt method.